Pockmark formation and evolution in deep water Nigeria: Rapid hydrate growth versus slow hydrate dissolution. Issue 4 (28th April 2014) - Sultan, N.; Bohrmann, G.; Ruffine, L.; Pape, T.; Riboulot, V.; Colliat, J.‐L.; De Prunelé, A.; Dennielou, B.; Garziglia, S.; Himmler, T.; Marsset, T.; Peters, C.A.; et al.
Abstract: In previous works, it has been suggested that dissolution of gas hydrate can be responsible for pockmark formation and evolution in deep water Nigeria. It was shown that those pockmarks which are at different stages of maturation are characterized by a common internal architecture associated to gas hydrate dynamics. New results obtained by drilling into gas hydrate‐bearing sediments with the MeBo seafloor drill rig in concert with geotechnical in situ measurements and pore water analyses indicate that pockmark formation and evolution in the study area are mainly controlled by rapid hydrate growth opposed to slow hydrate dissolution. On one hand, positive temperature anomalies, free gas trapped in shallow microfractures near the seafloor and coexistence of free gas and gas hydrate indicate rapid hydrate growth. On the other hand, slow hydrate dissolution is evident by low methane concentrations and almost constant sulfate values 2 m above the Gas Hydrate Occurrence Zone. Key Points: Free gas trapped in shallow micro‐fractures near the seafloor Very low methane concentrations above the top of the gas hydrate occurrence zone Pockmark formation controlled by rapid hydrate growth and hydrate dissolution